2013
DOI: 10.12944/carj.1.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Chlorophyll Content of Leaves

Abstract: In the present investigation, comparative studies have been done, to find the effect of air pollutants generated from the exhaust of industries and automobiles on the chrorophyll content of leaves. The leaves samples of Azadirachta indica, Nerium oleander, Mangifera indica and­ Dalbergia sissoo were collected from areas with potentially higher and lower levels of air pollution Photosynthetic pigments chlorophyll a, chlorophyll b and carotenoids were quantified. A reduction in the photosynthetic pigments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 10 publications
6
32
1
7
Order By: Relevance
“…Dusts emitted from kilns are highly noxious due to their alkaline nature and the associated metals. Several studies have shown how dust deposition can modify the species representativeness on tree trunks (Cieslinski and Jaworska 1986;Gilbert 1976;Wittman and Turk 1988) or depress physiological parameters of both lichens and higher plants (Kumar and Thambavani 2012;Giri et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dusts emitted from kilns are highly noxious due to their alkaline nature and the associated metals. Several studies have shown how dust deposition can modify the species representativeness on tree trunks (Cieslinski and Jaworska 1986;Gilbert 1976;Wittman and Turk 1988) or depress physiological parameters of both lichens and higher plants (Kumar and Thambavani 2012;Giri et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3). Em condições de estresse abiótico como déficit hídrico, a taxa de biossíntese de clorofilas tende a diminuir (Giri et al 2013). Os teores de clorofila total nas plantas in vitro, são mais baixos que quando encontrados na natureza e podem ser explicados pela dependência da única fonte de carbono do meio de cultivo (López-Escamilla et al 2016).…”
Section: Resultsunclassified
“…It might be due to the degradation of chlorophyll into pheophytin by the loss of magnesium ions. Leaf surface of trees in heavy polluted areas degraded chlorophyll content thereby reducing photosynthesis [5]. Thus any modification in chlorophyll concentration might change the morpho-physiological and biochemical activities of a particular species growing in roadside conditions.…”
Section: The Response Of Air Pollution Tolerance Index (Apti) and Othmentioning
confidence: 99%
“…The air pollution adversely impacts the photosynthetic pigment and consequently reduces productivity. Leaf chlorophyll, carotene, proline, and proteins are found to be influenced adversely by air pollutants [4][5][6][7][8]. The air pollution influences stomatal functioning and leaf thickness of urban plantation [9,10].…”
Section: Introductionmentioning
confidence: 99%